2002
DOI: 10.1590/s1516-89132002000200004
|View full text |Cite
|
Sign up to set email alerts
|

Arboreous vegetation of an alluvial riparian forest and their soil relations: Porto Rico island, Paraná river, Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 4 publications
0
19
0
5
Order By: Relevance
“…The low diversity of species in the diet of A. caraya on both the island and the mainland may be typical in this region due to the low diversity of plant species available in riparian areas on the Paraná River (CAMPOS & SOUZA 2002. Diet in both groups is quite restricted, even when considering low plant diversity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The low diversity of species in the diet of A. caraya on both the island and the mainland may be typical in this region due to the low diversity of plant species available in riparian areas on the Paraná River (CAMPOS & SOUZA 2002. Diet in both groups is quite restricted, even when considering low plant diversity.…”
Section: Discussionmentioning
confidence: 97%
“…data). The island has 38 species, 942-1,652 ind ha -1 and H' = 1.97 -2.24 (CAMPOS & SOUZA 2002. The "embaúba" tree Cecropia pachystachya Trécul is the most abundant species in the region, yet more abundant on the island than the mainland (M.C.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical regions the semi-deciduous forest is a type of forest, composed of meso-phanerophyte that covers, in general, sand-dystrophic soils (IBGE, 1992). The influence of the environmental variables in the floristic composition and structure of a semideciduous forest community are shown by the tendency of different survival strategies present in the environment (Campos and Souza, 2002). Campos and Souza (2002) found that the structure, dynamics and distribution of a species are related to the environmental characteristics, which determine the successful establishment and exclusion of certain species.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the environmental variables in the floristic composition and structure of a semideciduous forest community are shown by the tendency of different survival strategies present in the environment (Campos and Souza, 2002). Campos and Souza (2002) found that the structure, dynamics and distribution of a species are related to the environmental characteristics, which determine the successful establishment and exclusion of certain species. Therefore, the high diversity in the riparian areas is associated with the physical and chemical substratum variability and the interaction between the topography and hydrological regime of the watershed (Soares and Perez-Filho, 1997).…”
Section: Introductionmentioning
confidence: 99%